2016
DOI: 10.1371/journal.pone.0166810
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Quantification of Intracranial Aneurysm Pulsation with 4D CTA with Manual and Computer-Aided Post-Processing

Abstract: Background and PurposeThe analysis of the pulsation of unruptured intracranial aneurysms might improve the assessment of their stability and risk of rupture. Pulsations can easily be concealed due to the small movements of the aneurysm wall, making post-processing highly demanding. We hypothesized that the quantification of aneurysm pulsation is technically feasible and can be improved by computer-aided post-processing.Materials and MethodsImages of 14 cerebral aneurysms were acquired with an ECG-triggered 4D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…In our sample, the mean variation of the volume was 10.9% (95% CI 4% to 17%), but caution must be taken considering the variety in size of the aneurysms. Previous studies such as that by Illies et al 17 also investigated aneurysm volumetric changes during the cardiac cycle and concluded that volume changes remained unsettled considering the lack of a pulsation-like volume curve during the cardiac cycle and the lack of a gold standard with which to compare. They used a half-reconstruction mode (using half of the projections during the acquisition), which is known for inducing noise, consequently complicating the aneurysmal segmentation process 24.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our sample, the mean variation of the volume was 10.9% (95% CI 4% to 17%), but caution must be taken considering the variety in size of the aneurysms. Previous studies such as that by Illies et al 17 also investigated aneurysm volumetric changes during the cardiac cycle and concluded that volume changes remained unsettled considering the lack of a pulsation-like volume curve during the cardiac cycle and the lack of a gold standard with which to compare. They used a half-reconstruction mode (using half of the projections during the acquisition), which is known for inducing noise, consequently complicating the aneurysmal segmentation process 24.…”
Section: Discussionmentioning
confidence: 99%
“…All phases were reconstructed with a slice thickness of 0.5 mm and a 0.5 mm interval, 0.3×0.3 mm in-plane resolution, with a convolution filter (FC 43) designed for vascular imaging and hybrid iterative reconstruction performed with AIDR3D (Adaptive Iterative Dose Reduction 3D). The AIDR3D algorithm is based on iterative reconstruction, allowing dose and noise reductions 17 18. The pre-contrast volume was used to remove all the bony structures in the 20 arterial phases using subtraction techniques (figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Window/level settings are usually operator-specifically chosen. The resulting images and segmented structures are then used to calculate changes in volume over time or the like 16 18 . Such methods are, however, observer-dependent (in the case of a manual selection of thresholds).…”
Section: Cerebral Aneurysm Wall Motion Quantification: Overview Of Rementioning
confidence: 99%